Modelling muscle force distributions during the front and back squat in trained lifters - Sinclair, J.; Atkins, S.; Vincent, H.; Richards, J. D. (Central European Journal of Sport Sciences and Medicine, 2016)
The barbel squat ts a fundamental strength and conditioning exercise, with two principal variants; back and front. Whilst previous studies have examined the mechanical differences of the front and back squat, there Is no Information comparing the distributions of muscle forces between these variants. This study aimed to compare estimated forces developed bythe primary skeletal muscles used In the front and back squat. Twenty-five male participants were recruited with 6.24 ±2.21 years of experience in squat iftlng and 1 repetition maximum values of 127.5 ±18.8 and 90.6 ±14.4 kg for the back and front squat lifts. Participants completed both back and front squats at 70%of thelrfront squat 1 repetition maxim urn. Muscle forces were determined during dynamic situations using motion capture data, In addition to sagittal plane kinematics. Differences between squat conditions were examined using a multivariate analysis of variance. The kinematic analysis showed that the back squat was associated with significantly (p< 0.05) greater flexion of the trunk. Examination of muscles forces Indicated that erector splnae forces were also significantly (p< 0.05) larger In the back squat. No significant differences were Identified for skeletal muscle forces elsev/here (p>0.05). Our results Indicate that neither the front nor back squat provides any marked difference In muscle force production, aside from that Isolated to the lower back. These findings lead the conclusion that nether the front nor back squat conditions confer any additional benefits over the other In terms of the skeletal muscle force output.